PENDAMPINGAN PERENCANAAN DESAIN PENAMPUNGAN AIR HUJAN DI RPTRA KELURAHAN MERUYA SELATAN JAKARTA BARAT - Sri Novianthi Pratiwi; Punto Wijayanto; Ristya Arinta Safitri (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Environmental problems in the city of Jakarta are very complex. One of the problems is that the city  gets an abundance of rainwater while the availability of clean water is running low. Rainwater has great potential to be used for clean water reserves in buildings or public facilities. However, there are still many people who do not have the knowledge about how to collect and utilize rainwater, especially in the South Meruya area, West Jakarta. The manager of Child Friendly Integrated Public Space (RPTRA) that is located in South Meruya, West Jakarta, needs to be educated on the design of rainwater storage. The purpose of this Community Service is to provide knowledge to the management of the South Meruya RPTRA regarding the design of the rainwater harvesting system. The implementation method is carried out with an online meeting system. After the Community Service  activity was carried out, it was found that the RPTRA management of the South Meruya village had increased knowledge about the design of rainwater storage.